International Bibliographic Congresses - Lelikova, Natalia (Access: An International Journal of Nepal Library Association, 2024)
The article presents the IV International Bibliographic Congress, planned for September 2025 in Yakutsk (Russia), which will continue the tradition of similar great events held in Russia. First International Bibliography congress was held in 2010 in St. Petersburg, the second in 2015 in Moscow, and the third - in 2021 in Novosibirsk. It is shown that, by holding International Bibliographic Congresses, the Russian bibliographical community strives to achieve several goals: 1) identify cotemporary (at the time of the next congress) state of bibliography science and practice not only in Russia, but also in other countries of the world; 2) discuss the most pressing problems facing bibliographers; 3) outline the development of bibliographic activity for the near and distant future.